Tools for inventory control of dental supplies of a municipal health department - Fernando Silva Guimarães; Chazele Barbosa dos Santos; Letycia Barros Gonçalves; Leandro Leitzke Thurow; Marysabel Pinto Telis Silveira (Universidade Estadual de Campinas, 2019)
Aim: Carry out a descriptive and organizational analysis of the Oral Health warehouse of the Municipal Health Department in a city in the South of Brazil in order to assist in its management. Methods: This case study is a descriptive and organizational analysis of the Oral Health warehouse of the Municipal Health Department. The Always Better Control (ABC) curve, and Vital Essential Desirable (VED) analysis and ABC-VED matrix was performed, in order to assist the warehouse's management. The first stage was a descriptive situational analysis. In the second stage, the supplies were classified by the ABC curve and the VED analysis. Subsequently, the ABC-VED matrix was carried out. Results: Changes were made together with the local manager, such as organizing the products, labeling the items in the proper places and, carrying out the inventory more frequently (monthly). Furthermore, the method the first in, first out (FIFO) was applied. Of the 120 inputs, 13% corresponded to 65% of the expenditures (class A). In class B, close to 26% of the items accounted for 25% of the expenditures. Class C accounted for 10% of the costs and 61% of total materials. In the VED analysis, 19.2% of the items were classified as vital, and 62% and 19% as essential and desirable, respectively. In ABC-VED matrix, 23.3% (72%) belonged to category I, while 63% (25.6%) and 13% (2%) were classified in categories II and III, respectively. Conclusion: The use of inventory control tools granted a better storage of products and made it easier to find the items. The ABC curve, VED analysis and ABC-VED analysis allowed greater control, considering both cost and importance of supplies.